Metode Dongeng dalam Meningkatkan Perkembangan Kecerdasan Moral Anak Usia Prasekolah - Ahyani, Latifah Nur (Jurnal Psikologi: PITUTUR, 2010)
The research aims to know the storytelling method in increasing the development of moral intelligence  of  preschool  children.  Subject  of the  research  is  the  five  year  students  of kindergarten. The research is designed using model of The Untreated Control Group Design with Pretest and Posttest. This design uses two groups  examined  which  consist  of  an experiment  group  and  a  control  group.  The measurement is conducted twice using moral intelligence measurement instrument, namely before it is given treatment (pre-test) and after it has been given treatment (post-test). The result of  analysis  using  covariance  analysis (anacova)  shows  that  there  is  difference  of moral  intelligence  achievement  level  of  the preschool  children  between  those  who received  moral  value  guidance  using storytelling  method  and  those  who  do  not receive it. The result of analysis also shows that there  is  difference  of  moral  intelligence achievement  level  before  they  receive  moral value guidance through storytelling method and after the have received it. The importance of storytelling  method  toward  the  moral intelligence of preschool children is 34 %.